Pulse methylprednisolone therapy in Landau-Kleffner Syndrome - ARMAN, AYŞE (BUTTERWORTH-HEINEMANN, 1996)
Landau-Kleffner syndrome (LKS) is a subtype of acquired childhood aphasia associated with characteristic paroxysmal EEG recording of spikes and spike and wave complexes. The seizures, which start independently of the onset of aphasia, usually respond to antiepileptic drugs and have a good prognosis, but recovery of aphasia is variable. Steroid therapy has been recommended in recent years. We report an 8-year old girl with LKS who received intravenous high-dose methylprednisolone therapy without any side effect.
Keywords: Landau-Kleffner syndrome; methylprednisolone; pulse steroid; CHILDREN; APHASIA; EEG